Stem Cell Factor Neutralization Protects From Severe Anaphylaxis in a Murine Model of Food Allergy - Ptaschinski, Catherine; Rasky, Andrew J.; Fonseca, Wendy; Lukacs, Nicholas W. (Frontiers in Immunology, 2021)
Food allergy is a growing public health problem with approximately 15 million people affected in the United States. In allergic food disease, IgE on mast cells bind to ingested antigens leading to the activation and degranulation of mast cells. Stem cell factor (SCF) is mast cell growth and activation factor that is required for peripheral tissue mast cells. We targeted a specific isoform of SCF, the larger 248 amino acid form, that drives peripheral tissue mast cell differentiation using a specific monoclonal antibody in a model of food allergy. Ovalbumin sensitized and orally challenged mice were monitored for symptoms of anaphylaxis including respiratory distress, diarrhea, and a reduction in body temperature. During the second week of challenges, allergic mice were injected with an antibody to block SCF248 or given IgG control. Mice treated with anti-SCF248 had a decreased incidence of diarrhea and no reduction in body temperature suggesting a reduction in anaphylaxis compared to IgG control treated animals. Re-stimulated mesenteric lymph nodes indicated that anti-SCF248 treated mice had decreased OVA-specific Th2 cytokine production compared to IgG control treated allergic animals. The reduction of food induced anaphylaxis was accompanied by a significant reduction in gut leak. The mesenteric lymph node cells were analyzed by flow cytometry and showed a decrease in the number of type 2 innate lymphoid cells in mice injected with anti-SCF248. Morphometric enumeration of esterase+ mast cells demonstrated a significant reduction throughout the small intestine. Using a more chronic model of persistent food-induced anaphylaxis, short term therapeutic treatment with anti-SCF248 during established disease effectively blocked food induced anaphylaxis. Together, these data suggest that therapeutically blocking SCF248 in food allergic animals can reduce the severity of food allergy by reducing mast cell mediated disease activation.